Analisis Implementasi Peraturan Pemerintah Nomor 71 Tahun 2010 Tentang Standar Akuntansi Pemerintah (SAP) Berbasis Akrual dalam Penyusunan Laporan Pengelolaan Keuangan Daerah - Youdhi Prayogo; Atar Satria Fikri; Khairunnisa Puti Nandini (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2023)
This study aims to determine the implementation of Government Regulation Number 71 of 2010 concerning Accrual-Based Government Accounting Standards in the Preparation of Regional Financial Management Reports at the East Tanjung Jabung Regency Education Office. In this study using a qualitative descriptive approach that is trying to describe a complete social phenomenon. The data collection methods used were observation, interviews and documentation, then the data analysis techniques in this study were data reduction by selecting the main points, data display and data verification. The results of the study found that: The implementation of Government Regulation Number 71 of 2010 concerning Accrual-Based Accounting and Regional Regulations concerning Accrual-Based Accounting Policies in the Education Office's financial reports is that the Education Office in East Tanjung Jabung Regency has implemented accrual-based accounting which is accountability, financial transparency to the community (public) who have basic rights against the government, namely the right to know government policies, to know the decisions taken by the government, to know the reasons for carrying out certain policies and decisions, the right to be given information which includes the right to be given an open explanation of certain issues that become a public debate, and all of this has been carried out by the East Tanjung Jabung District Education Office by collaborating with non-public institutions with the mass media as a means of information flow for the community. The obstacle faced in implementing Government Regulation Number 71 of 2010 concerning Accrual-Based Accounting and Regional Regulations concerning Accrual-Based Accounting Policies in the Education Office's financial reports is that the Education Office in East Tanjung Jabung Regency still lacks professional Human Resources in managing finances, so training is needed to management staff.